Efektivitas Media Pembelajaran Sevima Edlink Terhadap Motivasi Belajar Siswa Pada Pelajaran Akidah Akhlaq di MA Islamiyah - Rifqi Maulana Rahman; Moh. Miftahul Choiri; Ahmad Shofiyuddin (Institut Kariman Wirayudha Sumenep, 2024)
Based on the results of the preliminary study observations in MA Islamiya Malo for class X there are 4 classes of 5 classes that have a lack of learning motivation more precisely in class X-2 there are still many students who are passive in learning, it is characteerizad by the number of students that are quiet and passive during the learning process, seen from the patteern of student interaction during learning, students tend not to pay attention to the teacher when the teacher explains the material in class. Increasing student learning motivation is a crucial component of learning succes. One alternative to increasing students’ desire to learn in today’s technology era is to use interactive learning media. The focus of this research is to find out how effective the use of interactive learning media based on Sevima EdLink against the learning motivation of students to learn at the eye of lessons Akidah Akhlaq fase E in MA Islamiyah Malo. The study involved all the students in the Malo Islamiyah MA X class, which totalled 135 people. The sample consited of 44 people, who were divided into two classes: one trial class with Sevima EdLink and one control class with books as the learning medium. The research data was collected through documentation, interviews, obsevations, and questionnaires of motivation statements for learning. Results of t-tedt data analysis show That There is a significan differenc betwen student learning motivation in the experiment class and the conrol class. This can be seen from the significance value of 0,023, which means<0,05 (sig<0,05). The average value of a student;s learning motivation questionnaire in an experimental class is 99,95, while the control class score is only 94,86. Study results show that Sevima EdLink improves students’ motivation to study phase E academic subjects in Malo’s Islamic MA. Students can improve their motivation for learning by using Sevima EdLink Which can make lessons more understandable and interesting.